Senyawa Triterpenoid dari Ekstrak N-heksana Daun Kelor (Moringa oleifera Lamk.) dan Uji Aktivitas Antibakteri Terhadap Staphylococcus aureus dan Escherichia coli - Salimi, Yuszda; Bialangi, Nurhayati; Abdulkadir, Widysusanti; Parulian, Boima Ramses (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
Kelor plant (Moringa oleifera Lamk) is a plant that grows naturally in a tropical climate. During this decoction of pirdot leaves plants are used by the people as antimicroba. The purpose of this study was to isolate triterpenoid compound from ethyl acetate extract of kelor leaves. The sample extraction was performed by maceration method using methanol as a solvent. Fractionation used n-hexana and etil asetat as a solvent. The separation and purification of the compound was carried out by column chromatography method followed by stain pattern analysis with thin layer chromatography (TLC). Characterization and elucidation of pure compound structures using UV, IR, 1H-NMR, 12C-NMR, HSQC, HMBC, and 1H-1H COSY, and compared with various literatures. Based on the result of structural elusidation, the pure isolate obtained is a pentacyclic triterpenoid group compound with the molecular formula C30H50O and the name of 3-hydroxy, 20 (29) -en, lupenol. The triterpenoid compound of 3-hidroxy, 20 (29) -en, lupenol is the first isolated and reported from leaves of kelor plant.